A Review of the Efficacy of Thalidomide and Lenalidomide in the Treatment of Refractory Prurigo Nodularis. Issue 3 (September 2016) - Lim, Victoria; Maranda, Eric; Patel, Vivek; Simmons, Brian; Jimenez, Joaquin
Abstract Prurigo nodularis (PN) is a chronic dermatoses characterized by intensely pruritic, excoriated, or lichenified nodules. Standard therapy includes corticosteroids, antihistamines, and phototherapy; however, treatment results are often inadequate or transient. Thalidomide and its analogue lenalidomide are immunomodulatory drugs that have successfully been used to treat refractory cases of PN. A systematic review was performed evaluating the use of thalidomide and lenalidomide for PN. Eighteen articles were included in this study in which a total of 106 patients were evaluated, of whom 76 (71.7%) had moderate to significant improvement of PN with the use of thalidomide, lenalidomide, or both. Patients given thalidomide were treated with doses of 50–300 mg daily for 1–142 months, with the majority being treated for less than 1 year. Patients treated with lenalidomide were given a daily dose of 5–10 mg from 3 to 24 months. The most common side effects observed were sedation, gastrointestinal symptoms, and transient peripheral neuropathy. While thalidomide and lenalidomide are drugs that have shown promising results in these studies, caution should be taken in prescribing these medications and patients should be informed about the potential side effects. As such, large-scale randomized controlled trials with long-term follow-up are needed to determine appropriate dosing, efficacy, and toxicity profiles.